Анализа корелације серумског PAPP-A2 и PIGF са прогнозом гестационог дијабетеса мелитуса: Серум PAPP-A2, PIGF са прогнозом гестационог дијабетеса мелитуса - Gao, Mengjie; Sheng, Xiaomei; Wang, Mengni; Gu, Xiaoxia; Yu, Hong; Huang, Tiantian; Zhang, Ling; Li, Wu; Gui, Yadi (Journal of Medical Biochemistry, 2026)
[Objective] To assess the diagnostic efficacy of the detection of serum Pregnancy-Associated Plasma Protein A2 (PAPP-A2), placental growth factor (PIGF), and secretory crimp-associated protein 5 (SFRP5) for detrimental effects of gestational diabetes mellitus (GDM) on pregnant patients. [Methods] 242 patients who received a GDM diagnosis at this hospital between January 2023 and December 2024 were chosen to be the GDM group. The normal pregnancy group consisted of 156 healthy expectant mothers who received prenatal care at this hospital over the same time frame. Patients in the GDM group were divided into the well-controlled diabetes group, the poorly controlled diabetes group and the high-risk group according to the level of glycated hemoglobin (HbA1c). Based on their follow-up results, patients in the GDM group were split into two groups: those with poor pregnancy outcomes and those with favorable pregnancy outcomes. Serum PAPP-A2, PIGF, Adipokine SFRP5, and urine microalbumin (mAlb) levels varied between the GDM and normal pregnancy groups. Univariate and multivariate analyses were used to analyze the factors influencing pregnancy outcomes and the relationships between the levels of serum PAPP-A2, PIGF, Adipokine SFRP5 and urine mAlb and the degree of blood glucose control and adverse pregnancy outcomes. In addition, it has diagnostic efficacy for adverse pregnancy outcomes in patients with GDM. [Results] Serum PAPP-A2, PIGF, and Adipokine SFRP5 levels were considerably lower in the GDM group than in the group with a normal pregnancy (P<0.01). The levels of serum PAPP-A2, PIGF and Adipokine SFRP5 in the well-controlled diabetes group were greater than those in the poorly controlled diabetes group and the high-risk group (P<0.01), although the level of urine mAlb was lower than that in the poorly managed diabetes group and the high-risk group (P<0.01). Compared to the group with good pregnancy outcomes, the group with poor pregnancy outcomes had significantly lower serum levels of Adipokine SFRP5, PIGF, and PAPP-A2 (P<0.01), while HbA1c, fasting blood glucose, and urinary mAlb levels were significantly higher in the poor pregnancy outcome group than in the good pregnancy outcome group. However, there was no statistically significant difference between the two groups in terms of body mass index, number of pregnancies, gestational age, or age (P>0.05). Serum PAPP-A2, PIGF, and Adipokine SFRP5 levels were protective factors against unfavorable pregnancy outcomes, according to multivariate logistic regression analysis (P<0.05), whereas the urinary mAlb level was a risk factor for adverse pregnancy outcomes (P<0.05). The efficacy of serum PAPP-A2, PIGF and Adipokine SFRP5 detection for the diagnosis of adverse pregnancy outcomes was significantly greater than that of urinary mAlb detection (P<0.05). With a sensitivity of 96.7%, specificity of 90.8%, and area under the curve (AUC) of 0.967, the combined detection approach outperformed the single indication PAPP-A2 by a substantial margin (Z=3.088, P<0.01). PIGF (Z=2.615, P<0.01) and Adipokine SFRP5 (Z=3.560, P<0.01) were included, but there was no statistically significant difference in the AUC among the three indicators (P>0.05). [Conclusion] The levels of serum PAPP-A2, PIGF and Adipokine SFRP5 are correlated with the degree of diabetes control in patients with gestational diabetes mellitus (GDM). Combined detection is helpful for improving the diagnostic efficacy for adverse pregnancy outcomes in GDM patients.